SOSIALISASI PENCEGAHAN COVID-19 DI PAUD SRIKANDI JAKARTA TIMUR MELALUI METODE CERITA BERGAMBAR - Uljanatunnisa Uljanatunnisa; Yani Hendrayani; Irpan Ripa'i Sutowo (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2021)
Early in 2020 the community was shocked by the Corona Virus Pandemic (Covid 19), it is estimated that more than 215 countries are struggling to stop the transmission of this virus, including Indonesia. This virus can attack anyone, including children, based on the results of case detection that children who have contracted Covid-19 also continue to increase. The Srikandi Early Childhood Education Institute, East Jakarta, has not provided Covid-19 education to its students. Through PKM activities, the Abdimas team of the Universitas Pembangunan Nasional Veteran jakarta carried out socialization activities for the prevention of Covid-19 including introduction to how to prevent Covid-19 through the pictorial story method. The series of activities consist of preparation, implementation and evaluation. Based on the results of the evaluation, it is concluded that the implementation of this activity is quite effective because the cognitive abilities of children have increased.